The Hybrid of Vertical and Horizontal Subsurface Constructed Wetlands for Greywater Treatment - Jery Permana; Anie Yulistyorini; Eko Suwarno (Center for Journal Management and Publication, 2022)
Greywater is categorized as domestic wastewater with a light pollutant concentration. The discharge of untreated greywater into the environment will decrease the environment quality, especially water bodies. This study aimed to investigate the performance of the combined vertical and horizontal sub-surface constructed wetlands in removing pollutants and recycling the greywater for a clean water alternative. The greywater sample was taken from the discharge point of the Rectorat Building of the Universitas Negeri Malang. The water bamboo plant (Equisetum hymale) was used in the experiment. The vertical sub-surface constructed wetlands dimensions were 50 cm in length, 50 cm in width, and 80 cm in height. While the horizontal one has dimensions 50 cm of length, 30 cm of width, and 30 cm of height. The water flowrate was designed to be 30 ml/min with a residence time of 3 days. The results showed that the hybrid constructed wetlands could reduce the pollutant concentration to meet the discharge consent. The efficiency of removal was TSS by 88% and BOD by 85%.